Formation of Widmanstätten ferrite at very high temperatures in the austenite phase field. (1st May 2016) - Grewal, Rupanjit; Aranas, Clodualdo; Chadha, Kanwal; Shahriari, Davood; Jahazi, Mohammad; Jonas, John J.
Abstract: Compression tests were carried out on a 0.06wt%C-0.3wt%Mn-0.01wt%Si steel at temperatures high in the austenite phase field. Eight deformation temperatures were selected in the range from 1000 to 1350 °C at 50 °C intervals. The quenched samples were examined using optical microscopy and EBSD techniques. It was observed that dynamic transformation took place and that the volume fraction of transformed ferrite first decreased with temperature (up to 1050 °C) and then increased as the delta ferrite temperature domain was approached. The EBSD results revealed the presence of Widmanstätten ferrite plates under all testing conditions, right up to 1350 °C. Graphical abstract: